Isolated Pulmonary Hydatid Cyst: A Rare Presentation in a Young Maasai Boy from Northern Tanzania - Jay Lodhia; Ayesiga Herman; Rune Philemon; Adnan Sadiq; Deborah Mchaile; Kondo Chilonga (Case Reports in Surgery)
Introduction. Hydatidosis is a parasitic manifestation caused by Echinococcus granulosus. It is characterized by cystic lesions in the liver and lungs. Diagnosis is based on typical history and radiological measures. Case presentation. A four-year-old boy presented with a one-year history of dry cough and difficulty in breathing which was of gradual progression. Computed tomography of the chest revealed a large 11.7 cm×8.6 cm×11.0 cm cyst in the right hemithorax. The patient underwent thoracotomy and recovered well post procedure. Conclusion. This case report highlights that large hydatid cysts can be surgically removed with good outcome and the importance of realizing that the disease is a burden to the public health and is much neglected.